Efeito de calcogenol ésteres em células planctônicas e biofilmes de bactérias orais - Sousa, Leonardo Silva de (2015)
Bacteria have a natural tendency to develop communities of cells surrounded by a polysaccharide matrix called a biofilm. Biofilms are formed on the surfaces of teeth (dental plaque) and are the main etiological factor for most dental problems such as caries, gingivitis and periodontitis. Dental plaque is made up of multiple species of bacteria that participate in the complex ecosystems of the human oral cavity. The genus Streptococcus is commonly found in the oral cavity, with emphasis on the species S. mutans and S. parasanguinis. In this context, research into new compounds capable of preventing or eradicating oral biofilms was intensified with these bacteria. This study aimed to evaluate the antibacterial and antibiofilm activity of 5 synthetic chalcogenol esters (S501, S502, S503, S505, S506) on S. mutans ATCC 25175 and S. parasanguinis ATCC 903. The effect of chalcogenol esters on planktonic cultures was determined by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Regarding biofilm formation, the compounds were added to bacteria at different concentrations (7.80 to 250 μg/mL) in microtiter plates. The plates were incubated for 24 h at 37°C on an orbital shaker at 120 rpm under atmospheric pressure, with 5% CO2. Biofilm formation was characterized by total biomass, using crystal violet staining, and the number of viable cells was expressed as log CFU/mL. Tests were also carried out with pre-formed biofilms with chalcogenol esters. The results showed that chalcogenol esters S505 and S506 presented MICs of 125 and 62.50 μg/mL, respectively, for S. mutans, while S501, S502 and S506 presented MICs of 62.50, 31.25 and 250 μg/ml for S. parasanguinis. Regarding biofilm formation, in general, all compounds effectively reduced the formation of biomass and the number of viable cells, mainly in S. parasanguinis and interfered with the pre-formed biofilm of both species. It was concluded that the tested chalcogenol esters have the potential to be an effective alternative against oral biofilms involving the species S. mutans and S. parasanguinis.